2008
DOI: 10.1002/adsc.200800303
|View full text |Cite
|
Sign up to set email alerts
|

Iminium Salt‐Catalysed Asymmetric Epoxidation using Hydrogen Peroxide as Stoichiometric Oxidant

Abstract: Iminium salt organocatalysts can provide high selectivity and high efficiency in catalytic asymmetric epoxidation. They are normally used in conjunction with Oxone as the stoichiometric oxidant. Oxone, however, has limited stability and is insoluble in most organic solvents; we report here for the first time the development of a reaction system driven by hydrogen peroxide as the stoichiometric oxidant, involving an unusual double catalytic cycle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…21 Olefin Epoxide yield / % % ee 84 92 96 97 65 89 Table 3. Asymmetric epoxidation of representative olefins using catalyst (27) Katsuki reported some excellent enantioselectivities for the catalytic asymmetric epoxidation 23 The different mechanisms proposed by Jacobsen and Katsuki account for the enantioselectivity observed. Lineker has also discussed the mechanistic aspects of the manganese-salen catalysed epoxidation.…”
Section: Jacobsen-katsuki Epoxidationmentioning
confidence: 99%
See 3 more Smart Citations
“…21 Olefin Epoxide yield / % % ee 84 92 96 97 65 89 Table 3. Asymmetric epoxidation of representative olefins using catalyst (27) Katsuki reported some excellent enantioselectivities for the catalytic asymmetric epoxidation 23 The different mechanisms proposed by Jacobsen and Katsuki account for the enantioselectivity observed. Lineker has also discussed the mechanistic aspects of the manganese-salen catalysed epoxidation.…”
Section: Jacobsen-katsuki Epoxidationmentioning
confidence: 99%
“…The Jacobsen-Katsuki epoxidation of alkenes involves a manganese-salen based catalyst Further probing of the ligands surrounding the manganese metal centre yielded catalyst (27) ( Figure 4), showing further increases in enantioselectivity. Jacobsen tested other oxidants, including commercial bleach, and found that epoxidation reactions at 4 °C yielded enantioselectivities above 90% ee for selected olefins (Table 3).…”
Section: Jacobsen-katsuki Epoxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…6 For example, epoxidation of cis-alkene 1 affords the corresponding epoxide 2 with 97% ee when employing iminium salt 3 (Scheme 3). 7 This system has since been used for the highly enantioselective total syntheses of levcromakalim [(-)-cromakalim], 7 (−)-(3'S)-lomatin, 8 (+)-(3'S,4'R)-transkhellactone, 8 We have also reported the use of hydrogen peroxide- 10 and sodium hypochlorite-11 driven systems for asymmetric oxaziridinium salt-mediated epoxidation. Both systems suffer from reduced rates of reaction and lower ees when compared to the original oxonemediated processes.…”
Section: Methodsmentioning
confidence: 99%